Фантазии на тему советника - Яблучанський, М.І. (Электронне видання, 2010)
The fantasies. On the advisor theme. The real and made-up experiences. With a practical goal. To support the administrative reform. Of the Central Executive Organs too. With the aim to improve standards of ordinary Ukrainians lives. Obligatory to improve life of Ukrainian officials. In order it to be with dignity - as they deserve. Фантазии. На советника тему. Опыты реальные и надуман- ные. С целью практической. Поддержать административ- ную реформу. Центральные органы исполнительной вла- сти тоже. Чтобы хорошо жилось пересічному українцю. И чиновнику обязательно. Чтобы с достоинством. Да по жизни. Заслужили давно.
The Aviser,s Theme Fantasies
Keywords: медицина; здравоохранение